Treatment Patterns and Blood Pressure Control With Initiation of Combination Versus Monotherapy Antihypertensive Regimens. Issue 1 (January 2021) - An, Jaejin; Luong, Tiffany; Qian, Lei; Wei, Rong; Liu, Ran; Muntner, Paul; Brettler, Jeffrey; Jaffe, Marc G.; Moran, Andrew E.; Reynolds, Kristi
Abstract : Many patients with hypertension require 2 or more drug classes to achieve their blood pressure (BP) goal. We compared antihypertensive medication treatment patterns and BP control between patients who initiated combination therapy versus monotherapy. We identified adults with hypertension enrolled in a US integrated healthcare system who initiated antihypertensive medication between 2008 and 2014. Patient demographics, clinical characteristics, antihypertensive medication, and BP were extracted from electronic health records. Antihypertensive medication patterns and multivariable adjusted prevalence ratios (PRs) of achieving the 2017 American College of Cardiology/American Heart Association guideline-recommended BP <130/80 mm Hg were evaluated for 2 years following treatment initiation. Of 135 971 patients, 43% initiated antihypertensive combination therapy (35% ACE [angiotensin converting enzyme] inhibitor (ACEI)-thiazide diuretics; 8% with other combinations) and 57% initiated monotherapy (22% ACEIs; 16% thiazide diuretics; 11% β blockers; 8% calcium channel blockers). After multivariable adjustment including premedication BP levels, patients who initiated ACEI-thiazide diuretic combination therapy were more likely to achieve BP <130/80 mm Hg compared with their counterparts who initiated monotherapy with ACEI (PR, 1.10 [95% CI, 1.08–1.12]), thiazide diuretic (PR, 1.21 [95% CI, 1.18–1.24]), β blocker (PR, 1.17 [95% CI, 1.14–1.20]), or calcium channel blocker (PR, 1.25 [95% CI, 1.22–1.29]). Compared with initiating monotherapy, patients initiating ACEI-thiazide diuretic combination therapy were more likely to achieve BP goals. Abstract : Supplemental Digital Content is available in the text.